2024
DOI: 10.3390/min14020118
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Vibrational Dynamics of Rutile (TiO2) from Molecular Dynamics Simulations and Two-Dimensional Correlation Analysis Techniques

Ljupcho Pejov,
Petre Makreski,
Gligor Jovanovski

Abstract: The vibrational dynamics of rutile (TiO2) as a function of temperature has been studied by combining molecular dynamics (MD) simulations in conjunction with the generalized two-dimensional correlation spectroscopy analysis (2D COS) technique. Molecular dynamics simulations within the microcanonical ensemble were performed with the self-consistent charge density functional tight binding formalism at a series of different temperatures. To validate the DFTB MD results against the experimental data, the method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In our recent study of rutile vibrational dynamics, a combined molecular dynamics (MD) approach, in conjunction with the linear response theory-based analysis of the trajectories, was carried out to compute the temperature-perturbed infrared response of TiO2 with the generalized twodimensional correlation analysis of the obtained spectra. 28 We have used the second-order selfconsistent charge density functional tight binding (SCC-DFTB) approach for 3D periodic systems to carry out the MD simulations. The study demonstrated the usefulness of the approach and its po-tential to get further insights into the vibrational dynamics of periodic systems by combining statistical physics simulations with the generalized twodimensional correlation spectroscopy (2D COS) analysis.…”
Section: T a B L Ementioning
confidence: 99%
“…In our recent study of rutile vibrational dynamics, a combined molecular dynamics (MD) approach, in conjunction with the linear response theory-based analysis of the trajectories, was carried out to compute the temperature-perturbed infrared response of TiO2 with the generalized twodimensional correlation analysis of the obtained spectra. 28 We have used the second-order selfconsistent charge density functional tight binding (SCC-DFTB) approach for 3D periodic systems to carry out the MD simulations. The study demonstrated the usefulness of the approach and its po-tential to get further insights into the vibrational dynamics of periodic systems by combining statistical physics simulations with the generalized twodimensional correlation spectroscopy (2D COS) analysis.…”
Section: T a B L Ementioning
confidence: 99%